Dangers and Risks of Plastic Screen Printing Work in Bolon Village, Colomadu District, Karanganyar Regency, Central Java Province - Wartini; Ani, Nur; Puspito Sari, Dewi (Universitas Muhammadiyah Surakarta, 2024)
Introduction : The screen printing process is carried out in a sitting working position and uses chemicals in the form of ink and thinner, with working hours starting from 07.00-17.00, depending on the amount of plastic being screen printed. The more plastic screen-printed, the longer the working hours will be used. Screen printers will face danger in every work activity. The risks that arise are poisoning due to the use of chemicals, experiencing musculoskeletal disorders due to ergonomic hazards, and work fatigue. Method: The type of research used is qualitative with a case study research design. The sampling technique was purposive sampling with three informants: The owner, Workers who took work home, and Workers who worked at the business owner's place. The variables studied include danger and the risk of danger to screen printing. Data collection techniques used interviews, observation, and literature study with triangulation methods. The instruments used were an interview guide, HIRA form, voice recorder, and camera. The collected data is analyzed by reducing, presenting, and concluding/verifying. Result: The research results show that the dangers arising from plastic screen-printing work are chemical hazards and ergonomic hazards. Risk analysis in plastic screen printing showed a high risk, namely central nervous system symptoms, and respiratory problems due to exposure to thinner (chemical) as a solvent. In contrast, the moderate risk was for ergonomic hazards with the risk of musculoskeletal complaints due to non-ergonomic work attitudes and twisting loads during the screen-printing process. Conclusion: Potential dangers in screen printing work are chemical hazards with a high risk and moderate risks for ergonomic hazards. It is hoped that this research can provide input to workers on using respirator personal protective equipment when working. Pendahuluan: Proses sablon dilakukan dengan posisi kerja duduk, serta menggunakan bahan kimia berupa tinta dan thiner dengan jam kerja mulai dari jam 07.00-17.00 bergantung dari jumlah plastik yang disablon. Semakin banyak jumlah plastik yang disablon akan semakin lama jam kerja yang digunakan. Penyablon akan menghadapi bahaya dari setiap aktivitas pekerjaannya. Risiko yang muncul adalah keracunan akibat penggunaan bahan kimia, mengalami gangguan musculoskeletal akibat bahaya ergonomis dan kelelahan kerja. Metode: Jenis penelitian yang digunakan adalah kualitatif dengan desain penelitian studi kasus. Teknik pengambilan sampel secara purposive sampling dan teknik pengambilan data menggunakan wawancara, observasi dan studi literatur dengan triangulasi metode. Analisis data dalam penelitian meliputi: reduksi data, penyajian data dan kesimpulan/ verifikasi. Hasil: Hasil penelitian diketahui bahwa hazard yang timbul dari pekerjaan penyablon plastic adalah bahaya kimia dan bahaya ergonomis. Analisis risiko didapatkan resiko tinggi pada proses sablon plastik dengan resiko terjadi gejala susunan syaraf pusat dan gangguan pernafasan akibat paparan thiner sebagai pelarut, sedangkan risiko sedang untuk bahaya ergonomis dengan risiko terjadinya keluhan muskuloskeletal akibat sikap kerja yang tidak ergonomis dan beban puntir saat proses pengerjaan sablon. Simpulan: Bahaya potensial pada pekerjaan sablon adalah bahaya kimia dengan risiko tinggi dan resiko sedang untuk bahaya ergonomi. Penelitian ini diharapkan dapat memberikan masukan kepada para pekerja untuk menggunakan alat pelindung diri respirator saat bekerja.